A New V-Based Metal–Organic Framework Synthesized from Pyrene-Based Linker - Tu, Thach N.; Tran, Nhung Thi (Journal of Technical Education Science, 2022)
A new vanadium based metal–organic framework (MOF), termed V-TBAPy, V2O2(C44H22O8)·9.5H2O, was designed and solvothermal synthesized. Crystal structure analysis showed that V-TBAPy is constructed from VO(CO2)2 rod-shaped SBUs (SBUs = secondary building units) and 1,3,6,8-tetrakis(p-benzoate)pyrene (TBAPy4–) linker to adopt the frz architecture highlighted by 1D channel of 9.3 Å and 4.0 × 9.4 Å2 in the structure. V-TBAPy was characterized by powder x-ray diffraction analysis (PXRD), thermal gravimetric analysis (TGA), Fourier transform infrared (FT-IR), elemental analysis (EA) and N2 adsorption measurements at 77 K. The resulted analyses indicated the highly thermal stability and permanent porosity of V-TBAPy with the Brunauer–Emmett–Teller surface (BET) area derived from the adsorption data of V-TBAPy to be 1620 m2 g–1. Furthermore, the rod-shaped morphology and the nano-size V-TBAPy were also confirmed by the scanning electron microscope (SEM) analysis suggesting the promising employment of the obtained material for adsorption and catalysis.